WhatsApp Grup Sebagai Media Komunikasi Kuliah Online - Reny Nabilla (UMSU, 2020)
In the midst of the Corona or Covid-19 Virus that hit Indonesia, the government issued a policy to temporarily shift the method of face-to-face learning in higher education to the implementation of online-based classes. Like the University of Lampung, the University of Lampung has an online lecture system. In this online lecture process the Whatsapp group feature is one of the media used in this online lecture process. The purpose of this study is to find out how the process and use of Whatsapp as a communication medium for online lectures at the Masters of Communication Sciences University of Lampung class of 2019. The method used in this research is descriptive qualitative method. In collecting this research data, observing whatsapp group. While the research data analysis technique is descriptive qualitative. The results of this study are the features of whatsaap group is a good alternative used in the online learning process. Lots of benefits arise and also students become active in class even though not doing face to face.